Study on Ultrasonic Response to Mechanical Structure of Coal under Loading and Unloading Condition - Xiaofei Liu; Xiaoran Wang; Enyuan Wang; Zhentang Liu; Xiaoyang Xu (Shock and Vibration)
Ultrasonic technology can be applied to study the changes in the internal defects of coal under quantitative loading, which can provide the theoretical basis for applying the technology to determine the structural stability of coal and predict disasters related to the dynamics of coal or rock. In this paper, to investigate the propagation laws of ultrasonic signals through a coal material under various loading conditions, an ultrasonic test system for the deformation and fracture of coal rock was used and a cyclic loading and unloading pattern is adopted. In addition, changes in ultrasonic parameters such as amplitude, dominant frequency, and velocity were analyzed. At the initial loading stage, the ultrasonic amplitude, amplitude of the dominant frequency, and wave velocity slightly decrease as the loading process progresses, and these three ultrasonic parameters gradually increase to their maxima when the stress level reaches approximately 46%. When it progresses from the linear elastic stage to the elastic plastic stage, the material inside the coal distorts and fractures more drastically, the inner defects are fully developed, and the acoustic parameters decrease significantly. Therefore, the corresponding measures should be adapted to reduce the loading stress before the coal is loaded to its critical stress level.